After Obasan:: Kogawa Criticism and Its Futures - Beauregard, Guy (Studies in Canadian Literature / Études en littérature canadienne, 2001)
One way of contributing to the growing body of cultural criticism that considers the cultural politics of emerging "ethnic canons" in Canada is through an examination of the large body of critical attention paid to Joy Kogawa's Obasan. Obasan can be understood as a symptom of how Canadian literary studies has attempted to reinvent itself by trying to address a "racial past" in a "multicultural present." Kogawa criticism should be at the centre of a contemporary rethinking of Canadian literary studies informing how critics have read and continue to read racialized texts and representations of histories of racism in Canada. It is also important to consider Asian American discussions of Obasan that are often informed by a tension between the cultural nationalist commitments of the Asian American movement and a concomitant desire to construct a coherent literary history with canonical texts.